Hypertensive crisis and pulmonary edema following rituximab-induced anaphylaxis - Brili, Stylian; Bei, Evangelia; Kounis, Nikolas G.; Chrysohoou, Christina; Antoniou, Christos-Konstantinos; Kontopidou, Flora; Bonfanti, Laura; Cervellin, Gianfranco; Tousoulis, Dimitrios Tousoulis; Tsioufis, Constantinos (Acta Biomedica Atenei Parmensis, 2021)
Rituximab is a monoclonal antibody against the protein CD20. Various lymphomas as well as non-malignant immune disorders are treated with this antibody. Hypersensitivity reactions associated with the use of rituximab include urticaria, hypotension, chest tightness, vomiting, oxygen desaturation and bronchospasm. A very uncommon case of hypertensive crisis and pulmonary edema following rituximab-induced hypersensitivity reaction in an 80-year-old man receiving rituximab for non-Hodgkin lymphoma is reported. Anaphylaxis manifesting as coronary vasospasm following drug treatment, including rituximab, could be proved a serious condition in patients who need specific treatment. In these patients desensitization protocols seem to be mandatory.